TREATMENT AND MANAGEMENT FOR SUICIDE ATTEMPT - Ketheeswaran, Yagatheeswaran (Bali Journal of Medical and Health Sciences; vol 1no1 2013, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 S uicid a l b e h a vior is a l e a ding c a use o f in j u r y a nd d ea th wo r ldwide. S uicide a t t e mpt is more p re v a lent a mo n g m e n, wh e re a s nonf a t a l suicid a l b e h a viours a r e more p re v a lent a mo n g wom e n a nd p e rsons who a re y ou n g , a re unm a r r i e d, or h a v e a p s y c hiatric d isord e r. D e spi t e a n inc rea s e in the tr e a t m e nt of suicid a l p e rsons ov e r the p a st d e c a d e , incid e n c e r a tes o f suicid a l b e h a vior h a v e re m a in e d l a r g e l y un c h a n g e d. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}